Importancia de la estimulación temprana y su incidencia en el desarrollo escolar de los niños y niñas de 0-4 años en la unidad educativa “francisco Aguirre Abad” del cantón Babahoyo de la provincia de los Ríos. - Barreros Guillin, Enma Esthela (2015)
This research conducted at the Center for General Education Basic "Francisco Aguirre Abad" Canton Babahoyo Los Rios Province, on the subject, Early Stimulation in the development and school adjustment of children of 0-4 years of basic education the same number of processes were performed to achieve respond to the issues raised in this investigation. For purposes of the research tree problem that the negative situation, of the problems and possible causes related effects were determined was performed. Han extensive literature search was performed and on the internet where substantial information from experts on the subject met: was validated to structure the framework, then the survey, parents and teachers, an observation guide was applied was applied to the students. To observe and control the process that took place. Later processes managed to check the results showed that adequate resources are made so, hampering the development and learning of children / as advantageously teachers are willing to receive training to update their knowledge to improve the process of stimulation and adaptation.